Mobile technology, farmer education and performance of agricultural projects: A case of the digifarm sunflower project in Makueni County, Kenya. - Jelimo, Ronoh Juliet; Gatotoh, Augustine Mwangi; Origa, Japheth Ododa (Universitas PGRI Madiun, 2024)
Mobile technology in agriculture offers an effective and economical means of expanding knowledge sharing and exchange. The purpose of this study was, therefore, to establish the influence of mobile technology on the performance of agricultural projects in Makueni County, Kenya. Specifically, the study remit was mobile applications and mobile money transfers. This study adopted a mixed-methods approach to ensure a comprehensive assembly and triangulation of requisite data to respond to the survey objectives. The target population for this study was all sunflower farmers in Makueni County who subscribed to the DigiFarm platform. The sample size for this study was 208. The results were presented using descriptive statistics and correlations between the variables studied. Mobile applications presented weak positive correlations with the performance of agricultural projects, while Mobile money presented a strong positive correlation with agricultural projects.